2017
DOI: 10.1108/jiabr-05-2015-0020
|View full text |Cite
|
Sign up to set email alerts
|

Financial development, Islamic finance and economic growth: evidence of the UAE

Abstract: Purpose Does Islamic finance affect economic growth? The empirical literature in this area seems to be in early stages and the results are often mixed and inconclusive. This paper aims to examine the causality between financial development in general, Islamic finance in particular and real economic growth in the United Arab Emirates (UAE). Design/methodology/approach Using time series data from 1990 to 2012, a bivariate vector autoregressive model was used to document the financial development-Islamic financ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
95
2
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(117 citation statements)
references
References 35 publications
9
95
2
11
Order By: Relevance
“…In general, the objectives of each MSMES development policy can be categorized into the following categories: For creation of an industry itself; supporting industry; Industrial sector reform; and employment [6]. In addition, Abdullah and Hoetoro further revealed that the purposes of the strategy to empower MSMEs are to [6]: (a) assist and provide incentives to MSMEs, (b) adjust industrial structures and provide suitable spaces for MSMEs for their survival and opportunities to grow [21], (c) respond to community needs because businesses can no longer focus solely on profits [22], (d) attention to individual and social balance [23].…”
Section: A Islamic Approach To Empower Micro Small and Medium Entermentioning
confidence: 99%
See 4 more Smart Citations
“…In general, the objectives of each MSMES development policy can be categorized into the following categories: For creation of an industry itself; supporting industry; Industrial sector reform; and employment [6]. In addition, Abdullah and Hoetoro further revealed that the purposes of the strategy to empower MSMEs are to [6]: (a) assist and provide incentives to MSMEs, (b) adjust industrial structures and provide suitable spaces for MSMEs for their survival and opportunities to grow [21], (c) respond to community needs because businesses can no longer focus solely on profits [22], (d) attention to individual and social balance [23].…”
Section: A Islamic Approach To Empower Micro Small and Medium Entermentioning
confidence: 99%
“…Thus, it is expected that MSMEs in Indonesia can continue to be supported to strengthen the community-based welfare. As a result, MSMEs in relation to the SDGs can become a pillar of creating various products and services needed by the community in order to improve the quality of their living standards [2,4,7,9,21,37].…”
Section: B the Role Of Msmes To Sustainable Development Goals (Sdgs)mentioning
confidence: 99%
See 3 more Smart Citations